Green public procurement: An empirical analysis of the uptake of organic food policy. Issue 3 (June 2022) - Lindström, Hanna; Lundberg, Sofia; Marklund, Per-Olov
Abstract: This paper analyses the uptake of a voluntary green public procurement policy in Sweden. The policy, decided in 2006, stated a national goal for the public sector to increase its share of organic food purchases to 25% by 2010. The overall purpose was to increase organic farming. Municipalities, which are highly independent authorities with self-determination, were encouraged to formulate own political goals. Based on survey data on organic food purchases for the period 2003–2016, supplemented with data on municipality characteristics, we analyse the determinants of the local uptake of the national policy, accounting for potential selection bias. The main finding is that local political goals are set and that these have in turn, a significant and positive effect on the share of organic food purchases. This suggests that there is an uptake of the voluntary policy. Also, we find that the increase in expenditures per capita devoted to organic food is quite substantial following the adoption of a local policy. Highlights: This paper studies the local uptake of a national voluntary organic food policy. Political ambitions have a positive effect on the share of organic food purchased. Adoption of the policy is associated with increased organic food expenditures. Financial factors and green awareness matter for the local uptake of the policy. Results are corrected for selection bias in the survey data.